2009
DOI: 10.1097/qad.0b013e32831f1b00
|View full text |Cite
|
Sign up to set email alerts
|

GBV-C viremia is associated with reduced CD4 expansion in HIV-infected people receiving HAART and interleukin-2 therapy

Abstract: Objective Interleukin-2 (IL-2) is a cytokine with multiple effects on lymphocytes including induction of CD4+ T cell proliferation. IL-2 administration has been shown to increase CD4 counts in HIV-infected people receiving antiretroviral therapy. GB virus C (GBV-C) is an apparently non-pathogenic flavivirus that replicates in CD4+ T cells and inhibits HIV replication in vitro by mechanisms including downregulation of HIV entry coreceptors (CCR5 and CXCR4) and induction of chemokines (RANTES, MIP-1α, MIP-1β, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 28 publications
5
48
0
Order By: Relevance
“…IL-2 is a key cytokine that promotes T cell activation, proliferation and supports HIV replication (reviewed in [69]). GBV-C viremic subjects had significantly reduced response to IL-2 therapy compared to GBV-C non-viremic subjects [70] suggesting GBV-C infection may alter IL-2 signaling pathways and affect T cell activation. Consistent with this, Berzsenyi et al found that intra-hepatic T cell signaling is impaired in GBV-C coinfected (HCV− and HIV−) positive individuals [71].…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-2 is a key cytokine that promotes T cell activation, proliferation and supports HIV replication (reviewed in [69]). GBV-C viremic subjects had significantly reduced response to IL-2 therapy compared to GBV-C non-viremic subjects [70] suggesting GBV-C infection may alter IL-2 signaling pathways and affect T cell activation. Consistent with this, Berzsenyi et al found that intra-hepatic T cell signaling is impaired in GBV-C coinfected (HCV− and HIV−) positive individuals [71].…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
“…In one study, GBV-C replication was diminished when PBMCs were cultured in IL-2 and PHA [7]. To examine the potential interaction between GBV-C and IL-2, study subjects participating in a prospective randomized trial of IL-2 were evaluated for GBV-C [70]. As in other studies, subjects randomized to receive intravenous (IV) IL-2 had significantly increased CD4 + T cell counts compared to those who received either subcutaneous IL-2 or no IL-2 [70].…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Both HPgV and the phylogenetically related hepatitis C virus (HCV) can establish persistent human infection through complex mechanisms that are not completely characterized (Gutierrez et al, 1997;Tanaka et al, 1998;Williams et al, 2004;Burke and Cox, 2010;Lemon, 2010). In HIV-infected humans, persistent HPgV coinfection is associated with reduced T cell activation, proliferation and function (Maidana-Giret et al, 2009;Schwarze-Zander et al, 2010;Stapleton et al, , 2009 suggesting that HPgV-mediated immune modulation may contribute to viral persistence. In vitro, HPgV envelope glycoprotein (E2) inhibits T cell activation by reducing signaling through the IL-2 receptor and the T cell receptor (TCR), with resultant reduction in activation of the lymphocyte specific tyrosine kinase (Lck) (Bhattarai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, GBV-C and HIV coinfection of lymphocytes also appears to inhibit the replication of R5-and X4-tropic HIV [11,36,37]. However, the exogenous addition of IL-2 and PHA to GBV-C-infected lymphocyte cultures resulted in decreased GBV-C replication [38]. Although at present it is understood that spleen and bone marrow are the primary sites of replication [39], investigations are underway to completely exclude the role of other sites and cells, especially liver cells, as possible sites of replication.…”
Section: Gbv-c Replicationmentioning
confidence: 99%